Uwarunkowania liberalizacji stanowisk wobec narkotyków oraz ich zażywania zidentyfikowane w środowisku szkolnym – dane z badań - Motyka, Marek A. (Studia Edukacyjne, 2019)
Over the past few decades, researchers of drug addiction have drawn attention to the unprecedented dynamics in the positions on drugs and a growing number of people who admit to the use of such substances for hedonistic and recreational purposes. An intensification of drug addiction led to the identification of a large number of drug-related problems which occur on individual, social and global levels. The last decade has abounded in seemingly uncontrollable, numerous events linked mainly to the spread of “legal highs”. These events included: legal trade in those products in Poland, two waves of numerous deaths associated with their use, the extremely unscrupulous distribution of “legal highs” through websites, and particularly the liberalisation of attitudes towards those new designer drugs. The considerable importance in creating positions in favour of drug use should also be attributed to the popularity of marijuana, increasingly gaining a status of a recreational drug. This paper discusses the current reasons why the youth begin to use drugs as identified in the school environment. The research focused on obtaining reliable data allowing to diagnose the phenomenon of drug use by the young people in Podkarpacie Province and to determine factors contributing to drug initiation among this segment of population. In the quantitative research, the empirical data were collected through a specially designed questionnaire from a random sample of young people from 27 secondary schools in Podkarpacie Province (n=2237). Within the sample, 712 students (31%) admitted to using drugs. The most important educational factors for promoting psychoactive substances are low involvement in education and frequent school absences. Drugs are more commonly used by older students. The research material presented in this article can be successfully used by practitioners in the field, including sociologists, educators and psychologists, and by institutions active in social prevention. It can also form the starting point for further explorations of this important social phenomenon.